Marketable Title to Real Estate Being Also a Treatise on the Rights and Remedies of Vendors and Purchasers of Defective Titles, including the Law of Covenants for Title, the Doctrine of Specific Performance, and Other Kindred Subjects (1896)
Summary goes here